Penetapan Perayaan Suci: Kajian Terhadap Imamat 23:1-5 - Lisda Waty Harianja; Marco Menang Iman P Padang (Jurnal Magistra, 2023)
This study delves into Leviticus 23:1-5, which outlines the establishment of sacred celebrations within the Jewish religious tradition. This passage details a series of celebrations specifically ordained as sacred moments within their religious calendar. An analysis of this text reveals the significance of these celebrations in shaping the spiritual and social identity of the community, as well as the values they uphold. Leviticus 23:1-5 provides clear guidelines regarding the timing, purpose, and importance of observing these events within the Jewish religious life, offering insights into their underlying religious values.